Rancangan Dinding Interaktif Vokasi Berbasis Human Centered Design dengan Pengukuran User Experience Questionnaire - Tarihoran, Jeremy Amanda Putra; Mu'minin, Amirul (Jurnal Sosioteknologi, 2025)
The Augmented Reality (AR)-based Vocational Interactive Wall is designed to showcase content from the Directorate General of Vocational Education, including profiles and innovative works through an interactive wall. This application aims to provide a more immersive and engaging experience, allowing visitors to play, learn, and have fun simultaneously using AR technology. The purpose of this research is to assist students and visitors in exploring the profile of the Directorate General of Vocational Education through an AR-based interactive medium. The study employs the Human-Centered Design (HCD) method for product development and the User Experience Questionnaire (UEQ) for evaluating user satisfaction. Data were collected from 20 respondents during the Vokasi Fest x Kampus Merdeka 2023 event. The analysis results indicate that the AR-based Vocational Interactive Wall application is deemed "suitable" for use, offering an engaging and interactive user experience. These findings highlight the application's potential as an innovative learning medium that effectively enhances engagement in educational settings.